STUDY OF ASSOCIATION BETWEEN COGNITIVE IMPAIRMENT AND GLYCEMIC CONTROL IN TYPE 2 DIABETES PATIENT AND MOCA (MONTREAL COGNITIVE ASSESSMENT) AS A PREDICTIVE TOOL FOR GLYCEMIC CONTROL IN DIABETIC PATIENTS WITH COGNITIVE IMPAIRMENT: A CROSS-SECTIONAL STUDY - BHOSALE, UMA; DHARAP, NEHA; GADAVE, ATHARV (International Journal of Current Pharmaceutical Research, 2025)
Objective: India has the second highest number of type 2 diabetes mellitus (T2DM) cases, with several known complications, including heart disease, stroke, hypertension, atherosclerosis, neuropathy etc. In a considerable number of diabetics, cognitive impairment is found. This prevalent complication is an alarming one. There has been insufficient research data to conclusively comment on cognitive impairment in diabetic patients with poor glycemic control. This study was therefore designed to assess the cognitive impairment using MoCA test (Montreal Cognitive Assessment) and its association with glycemic control in T2DM and utility of MoCA test as a predictive tool for glycemic control in patients with cognitive decline over period of time. Methods: 30 points MoCA test was conducted in 150 T2DM patients. Results: In present study, significant cognitive impairment (MoCA score<26) was found in diabetic patients with HbA1c % >7.5 and a resounding majority of diabetic patient also showed cognitive impairment with greater preponderance towards the uneducated subjects and those with co-morbid conditions. Conclusion: The diabetics with strict glycemic control have lesser incidence of cognitive impairment over period of time. MoCA test could be used as early predictive tool for glycemic control in patients with cognitive decline.